Breeding of the facultative barley varieties at the FSBSI ARC «Donskoy» - A. A. Dontsova; D. P. Dontsov; E. G. Filippov (Зерновое хозяйство России, 2023)
The current paper is devoted to the study of promising barley lines with an alternative type of development (facultative). Famous breeders P. F. Garkavy and V. M. Shevtsov believed that the future belonged to the facultative barley varieties, since they had high adaptive properties. Facultative varieties have several advantages, such as they can be used for early spring reseeding of sparse autumn crops of winter barley with seeds of the same variety and dead crops of winter cereals, as well as for obtaining high-quality seeds from spring sowing for autumn sowing. In connection with the above, the cultivation of facultative varieties for production is of great relevance and necessity. The purpose of the current study was to estimate new breeding material for facultative barley varieties in the conditions of the south of the Rostov region. The study was carried out in 2021–2023 in the fields of scientific crop rotation of the department of barley breeding and seed production of the ARC «Donskoy». In the first competitive variety testing there have been studied 12 promising facultative barley lines and the two currently best facultative barley varieties ‘Step’ and ‘Marusya’. There has been carried out comprehensive estimation of the studied samples based on such traits as the length of a vegetation period, resistance to lodging and damage by leaf diseases, 1000-grain weight, number of grains per an ear, number of productive stems per square meter, productivity. According to lodging resistance on average over three years, there were identified the varieties ‘Marusya’ and ‘Step’, as well as the lines Parallelum 2019, 2139, 2110, 2128, 2152, 2153 and Pallidum 2100; according to grain size the best varieties and lines were ‘Step’, ‘Marusya’, Parallelum 2141, 2110, 2128, 2149, 2152 and Pallidum 2100. The variety ‘Marusya’ and the lines Parallelum 2139, 2128, 2136, 2110, 2149, 2152, 2153 have shown the greatest productivity increase of 1 t/ha to the standard. Based on the data obtained, all studied varieties received a score based on a complex of economically valuable traits. The variety ‘Parallelum 2128’, which received the maximum number of points, was selected, and prepared for sending to the State Variety Commission of the Russian Federation for study.